Acute appendicitis after motor vehicle collision - Sean M. DuBois; Lauryn A. Ullrich (Trauma Case Reports)
Acute appendicitis is the most common abdominal surgical emergency today. Blunt abdominal trauma is a rare etiology of appendicitis, with a reported incidence of 0.3–0.9 %. Traumatic appendicitis is more common in the pediatric population, with a median age of 11.5 years. We present the case of a 13-year-old healthy female who presented as a trauma activation after a motor vehicle collision. Clinical examination revealed ecchymoses and abrasions over bilateral hips consistent with a seatbelt sign, with tenderness in the periumbilical region and right lower quadrant. Imaging was consistent with developing appendicitis. The patient was taken to the operating room for laparoscopic appendectomy; a long, dilated, and inflamed appendix was identified intraoperatively. She did well postoperatively and was discharged home from the post-anesthesia care unit. It is important to maintain a high clinical index of suspicion for appendicitis and similar diagnoses when evaluating the pediatric trauma patient.